DIAGNOSTIC EVALUATION OF FERRITIN DEFICIENCY IN CARDIOVASCULAR DISEASE PATIENTS - Parigela Prasanth; B. Kiran Kumar Reddy (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The occurrence of Iron Deficiency (ID) in heart failure significantly impacts morbidity and mortality. This study assesses ferritin deficiency among HF patients, comparing iron metabolism parameters between individuals with and without ID. A cohort of 140 participants, comprised of both males and females, were evaluated. Blood samples were collected to measure hemoglobin (Hb), A total profile consists of ferritin, serum iron, total iron-binding capacity (TIBC), and transferrin saturation (TSAT). It was found that there were statistically significant differences in ferritin (p=0.01), serum iron (p=0.05), and TSAT (p=0.04) levels between ID and non-ID groups, with ID patients demonstrating markedly lower levels in these parameters. Ferritin levels averaged 80.6 ng/ml in the ID group versus 274.6 ng/ml in the non-ID group, underscoring ferritin’s role as a critical marker of iron storage. Similarly, reduced serum iron and TSAT levels in ID patients reflect diminished iron transport and availability. Although Hb and mean corpuscular volume (MCV) values showed Lower trend but not significant levels in ID patients (p=0.12 and p=0.17 respectively), these parameters alone were inadequate for diagnosing ID. The findings emphasize the diagnostic utility of ferritin, serum iron, and TSAT levels in assessing iron deficiency among HF patients.